쿠민 종자 에탄올 추출물이 산화방지 및 유지 산화안정성에 미치는 영향 - 김민아(Min-Ah Kim); 한창희(Chang Hee Han); 김미자(Mi-Ja Kim) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2018)
This study aimed to investigate the antioxidant ability of a cumin seeds ethanol extract (CE). The DPPH and ABTS radical scavenging activities of 0.25, 0.5, and 1.0 mg/mL of CE were found to be 24.6, 41.4, and 73.4 and 14.5, 27.2, and 50.1%, respectively (p<0.05), suggesting a dose-dependent effect. Moreover, the total phenolic content of CE was 61.0 μM tannic acid equivalent/g extract and the FRAP value was 429 μM ascorbic acid equivalent/g extract. In 9 hours of oil oxidation, CDA and ρ-AV was significantly reduced to 13.4 and 59.1%, respectively, at a CE concentration of 100 ppm compared with that in the control (p<0.05). Major volatile compounds of CE were found to be α-pinene, 2-butenal, cyclohexene, β-pinene, cis-sabinene, ρ-cymene, and limonene. These results suggest that CE containing volatile compounds has excellent antioxidant ability and oxidation stability, and thus could be used as a natural antioxidant to prevent oxidation in lipid foods.